The Useful Passion: Death and the Meaning of Life in Miguel de Unamuno - Gutiérrez Pozo, Antonio (2023)
The bourgeois attitude towards death is to postpone it and forget it. The meaning of our existence is, then, to lengthen life as much as possible. Heidegger understands death as the most authentic possibility of human beings: human beings are there to die. In Unamuno the desire to live of the hunger for immortality is grounded on the awareness of having to die; at the same time, having to die implies the hunger for immortality. This is the tragic sense of life. Absolute death implies the complete lack of sense. Thus, human beings would be a useless passion. In the hunger for immortality there is, therefore, a profound affirmation of the meaning of life as a struggle for meaning. Although nothingness awaits us, let’s turn this into an injustice: that is, act in such a way that you do not deserve to die, that you deserve eternity and meaning. Against the metaphysical nihilism of Mephistopheles, hope is thus grounded. Therefore, this passion is useful since we are only able to relate to eternity and meaning by deserving them.